Optimal kVp Selection for Contrast CT Imaging Based on a Projection-domain Method - Rui, Xue (Conf Proc Int Conf Image Form Xray Comput Tomogr, 2014)
Computed Tomography (CT) has been in clinical use for several decades. The number of CT scans has increased significantly worldwide, which results in increased radiation dose delivered to the general population. Many technologies have been developed to minimize the dose from CT scans, including scanner hardware improvements, task-specific protocol design and advanced reconstruction algorithms. In this study, we focused on selection of X-ray tube voltage and filtration to achieve optimal dose efficiency given required image quality, more specifically the contrast to noise ratio. Our approach differs from previous studies in two aspects. Typically, Monte-Carlo simulation is used to estimate dose in simulations, but this is computationally costly. We instead use a projection-domain dose estimation method. No image reconstruction is required for the projection-domain method, which further simplifies the analysis. This study also includes tantalum, a new contrast agent, in addition to soft tissue (water), bone and iodine contrast. Optimal tube voltages and filtration are identified as a function of phantom size. The simulation analysis is confirmed with a limited phantom study.